MANAGEMENT OF THE IMPLEMENTATION OF THE MAGRIB PROGRAM OF RECURRING AT THE MOSQUE - Said, Salim (Universitas Islam Negeri (UIN) Sumatera Utara, 2023)
The Maghrib Koran Movement is a program issued by the central government and local governments. This program focuses more on children and youth, where children and adolescents in urban areas can use their maghrib time by reciting the Koran, not with unnecessary activities and get adequate education. . Then there are efforts that can be made by the manager in improving the implementation of the Maghrib recitation, namely making reading the Al-Qur'an the main activity. From this recitation activity the manager of the magrib recitation program tries to improve the implementation of the recitation magrib in order to improve the quality of good children for the future.